A methodological approach for the on-site quantification of food losses in primary production: Austrian and German case studies using the example of potato harvest. (1st March 2019) - Schneider, Felicitas; Part, Florian; Göbel, Christine; Langen, Nina; Gerhards, Christian; Kraus, Günther F.; Ritter, Guido
Graphical abstract: Highlights: A quantification method has been developed to determine food losses on the field. The applicability of the method was assessed in the framework of six case studies. Between 1% and 10% of field losses can be generated during the potato harvest. Abstract: In the last decade, in many European Countries more and more measures have been initiated aiming at the prevention of food losses and wastes along the entire value chain. In order to evaluate or monitor such important measures it is crucial to obtain quantitative information on generated food waste amounts, subsequently enabling the quantitative evaluation of the measure's outcomes and efficiency. Currently there is a paucity of quantitative information, particularly on food losses that are directly generated during harvesting processes. Up to date, no method is available or standardised aiming at the in-situ or on-site quantification of food losses during harvest. Using the example of the potato harvest, this study presents a practical approach for determining potato losses. To test the applicability of the developed method, on-site measurements were conducted directly on the field at five different locations in Austria and Germany. Our method enables the quantification of food losses based on defined areas along the harvested potato rows, where the analyser manually collects potatoes during their harvest. Hereby, two types of potato losses needs to be considered: non-harvested, under-sized potatoes that remain under the earth and the harvested ones, which are rejected on-site because of quality requirements regarding their size, shape, and state of health. Our study shows that between 1 and 9% of field losses (based on yield potential) can be generated during the potato harvest. In future, this method may be the basis for standardised protocols in order to be able to derive cultivar-specific benchmarks and, consequently, to develop measures for preventing food losses. In general, more case studies and evidence-based ground-up measurements on other cultivars and for other regions are needed focusing on the on-site quantification of post-harvest losses.